Sound therapy using quranic verse in increasing the calmness and reducing stress on final year students in UNIMAS - Normardina, Abdul Rahim (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The research aims to evaluate the efficacy of neurofeedback training as a sound therapy using Quranic verse. Five students were purposely selected for this research. A quasi experimental research involving a series of observation and interpretation of results from a data acquired from QEEG recording and neurofeedback training sessions was used to observe the effect of the treatment on the participants that have stress. An average of 14 sessions of neurofeedback training has been conducted in this study. For delta protocol, the reward frequency was delta, as low inhibit was beta and high inhibit was hi beta. This protocol was used in the 1st session to 4th session. While for beta protocol does consist of theta as the low inhibit, beta was the reward frequency and hi beta as the high inhibits frequency. This protocol was used in the 5th session until 14th session. Before the neurofeedback training session is conducted, pre-test QEEG was conducted to determine the appropriate protocol and placements of electrode for the purposed of neurofeedback training. Post-test QEEG was conducted after neurofeedback training sessions to look the changes in brain wave patterns and the effectiveness of al-Quran verses as sound therapy.